Eksplorasi Pelayanan Informasi Yang Dibutuhkan Konsumen Apotek Dan Kesiapan Apoteker Memberi Informasi Terutama Untuk Penyakit Kronik Dan Degeneratif - Handayani, Rini Sasanti; Gitawati, Retno; Muktiningsih, S.R; Raharni, Raharni (UI Scholars Hub, 2006)
Currently, the prevalence of degenerative diseases in Indonesia is increased. The degenerative and chronic diseases need life-long treatment as well as changes in life style. On the other hand, long-life treatment using drugs will develop risks of adverse drug reactions or the possibilities of drug-drug interactions. In these circumstances, the role of a pharmacist is important to providing drug information and counselling, and patient education. However, there is evidence that pharmaceutical care in almost all pharmacies (drug dispensaries) in Indonesia is still drug-oriented. Drug information is not adequate and is provided by pharmacy assistants (technicians). In order to implement pharmaceutical care practice that meets the Standard Competence for Pharmacy Practice as well as consumers expectation, we need to know what is the exactly consumers expect in pharmaceutical care, particularly in drug information, and how is the commitment of the pharmacists to provide drug information of degenerative and chronic diseases in pharmaceutical care. For those reasons, a field survey has been carried out in Jakarta, Yogyakarta and Makassar to explore the consumer/patients opinions and needs for pharmaceutical care. A focus group discussion has also been done to explore the pharmacist commitment to provide drug information in pharmaceutical care practice. As a result, there is an indication of a discrepancy between the consumer/patients need for drug information and the commitment of pharmacists to provide drug information. Consumers have need for more drug information for all aspects including adverse drug reactions, drug interaction, what to do if adverse reaction occurred, duration of any treatments etc., not only drug indication and administration. On the other hand, pharmacists still need more knowledge and continuing education, particularly in pharmacotherapy and pharmacology of drugs used for degenerative and chronic diseases.